Perbaikan Desain dan Informasi Kemasan Yoghurt Kecombrang Sebagai Upaya Meningkatkan Daya Saing Produk UMKM Yoghurt Sehati - Rifda Naufalin; Rumpoko Wicaksono; Icuk Rangga Bawono; Muhammad Yusuf Nugroho; Popi Nurhopipah (Politeknik Piksi Ganesha Indonesia, 2025)
One way to develop Micro, Small and Medium Enterprises (MSMEs) through higher education is by carrying out community service. Yoghurt Sehati MSMEs face obstacles in increasing the competitiveness of their products in an increasingly competitive market. Product packaging that is still simple is considered less able to attract consumer attention and needs to be improved in order to compete more effectively. This community service program aims to assist Yoghurt Sehati MSMEs in improving the design and information on their product packaging. The methods used in this service include socialization of activities, introduction of new labels and packaging, training and effective business development assistance. The community service team carried out activities that included improving packaging labels, introducing more informative packaging, and entrepreneurship training. Through this community service activity, the condition of MSMEs can improve, MSME knowledge increases, and marketing becomes more effective.